Frequency of Helicobacter pylori infection in patients attended at Centro de Salud Ocaña, Ayacucho - Chávez Barriga, John (2020)
Objectives: To determine the frequency of Helicobacter pylori infection in patients attended at Centro de Salud Ocaña, Ayacucho. Methods: A cross-sectional study was performed in patients at whom a rapid H. pylori Ab was carried-out from July to December 2017. Results: The frequency of H. pylori was 67.3%, the frequency of infection by age group was 62.5%, 52.9%, 68.1%, 72.7% y 76.9% in adolescents, young adults, elder, and pregnants, respectively. The frequency of infection by sex was 74.5% and 64.8% for males and females, respectively. Conclusions: The frequency of H. pylori infection found in this study is higher than that reported from developed countries, but similar to that found in South American countries, no significant differences by age and sex were found.